PERLINDUNGAN SAKSI PERKARA PERCERAIAN YANG MEMBERIKAN KETERANGAN DALAM PERSIDANGAN - Muh Sutri Mansyah; La Ode Bunga Ali (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2023)
Witnesses who provide testimony at divorce trials often experience threats and even legal action. Meanwhile, regulations regarding witness protection are still inadequate. The aim of the research is to analyze and examine the urgency of protecting witnesses in giving information in divorce cases in religious courts and what is the best model for witness protection. The research method used is normative juridical using a statutory approach, primary data namely the Witness Protection Law and the 1945 Constitution of the Republic of Indonesia. The results of the research state that the role of witnesses in divorce cases is very important, but witnesses need protection based on 709 requests for non-criminal cases rejected by the Protection Agency Witnesses and Victims (LPSK) because it is not their authority in the Witness and Victim Protection Law and criminal witnesses are the only ones regulated in the Witness and Victim Protection Law so that non-criminal witnesses cannot be protected even if a request for protection of non-criminal witnesses is found. The shift in legal interests in divorce cases does not depend on the Plaintiff or Defendant, but the presence of witness protection needs to be considered. After all, witnesses are a form of evidence that must be given their rights. There is a vacuum in the law for witness protection in divorce cases, so it is necessary to revise the Witness and Victim Protection Law in the future.